Cooling strategies improve intermittent sprint performance in the heat of athletes with tetraplegia. Issue 6 (14th June 2008) - Webborn, N; Price, M J; Castle, P; Goosey-Tolfrey, V L
Abstract : Background: Precooling has been shown to enhance performance in repeated sprint exercise in able-bodied subjects in a hot environment. Spinal cord injury causes thermoregulatory impairment with a detrimental effect on performance. This study assessed whether cooling strategies before and during exercise in the heat enhances sprint performance in athletes with tetraplegia. Methods: Eight male athletes with tetraplegia performed intermittent arm crank exercise in the heat (32.0°C (0.1°C); humidity, 50% (0.1%)) for a maximum of 60 min or until exhaustion. Trials involved a no-cooling control (CON), precooling (PRE) or cooling during exercise (DUR). Each intermittent sprint protocol consisted of varied periods of passive rest, maximal sprinting and active recovery. Results: Both PRE and DUR cooling strategies improved the ability of the athletes to repeatedly perform high-intensity sprints, with times to exhaustion (TTE), whereas during the CON trial, athletes demonstrated a reduction in the total number of sprints and TTE (47.2 (10.8), 52.8 (5.8) and 36.2 (9.6) min for CON, PRE and DUR, respectively). Core temperature was significantly higher for CON (37.3°C (0.3°C)) when compared with both PRE and DUR (36.5°C (0.6°C) and 37.0°C (0.5°C), respectively, p<0.01). Ratings of perceived exertion and thermal sensation upon exhaustion or completion were not different. Conclusions: Athletes with tetraplegia should use a precooling or during-exercise cooling strategy specific to the characteristics of their sport when exercising in hot conditions.